Perlindungan Hukum Terhadap Konsumen Pada Jual Beli Online Pre-Order di Aplikasi Facebook dalam Perspektif Hukum Ekonomi Syaiah (Studi Kasus di Desa Salulino Kec.Walenrang Utara Kab. Luwu) - A, Nurfadila; Raehana, Syarifa; Lawang, Hasanna (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In Salulino Village, North Walenrang District, Luwu Regency, this phenomenon is being utilized by young people and housewives as a means of e-commerce to meet economic needs and generate additional income.This research aims to understand the online pre-order buying and selling transactions on the Facebook Application of the Salulino Village Community in Walenrang Utara District, Luwu Regency, and how consumer rights protection is provided according to the consumer protection laws and sharia economic law. Using data collection techniques of interviews and documentation, it analyzes the data by reducing to extract important data, presenting the data in descriptive form, and drawing conclusions.The research findings revealed online pre-order sales transactions on the Facebook Application in the community of Salulino Village, North Walenrang District, Luwu Regency. There is an agreement between sellers and buyers regarding the objects being sold. The seller includes item details in their Facebook posts, with payment being made in full at the beginning and the delivery of goods through shipping services. This type of transaction falls under the category of bay' al-ma'dum because the goods are not available at the time of the contract. The method of full payment in advance is similar to a salam contract. Consumer protection is regulated in Law No. 8 of 1999 concerning consumer protection. In online pre-order sales transactions in Salulino Village, North Walenrang District, Luwu Regency, it shows that business actors have fulfilled their obligations in providing clear information and honest service